(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study was carried out on six Iraqi breed rams, aged between 2 to 4 years, during the period from Nov. 2018 to the Mar. 2019. Semen samples were collected from each ram with electro ejaculator at the morning, one ejaculate per week over a time of 16 weeks. Pooled semen for all rams were used to evaluate the characteristics of semen to avoid individual variation between the animals. The volume and the color offresh semen was recorded directly, then semen was evaluated for mass and individual motility, live/dead percentage and sperm abnormalities. Semen samples were diluted 1:10 with a Tris-based extender, and divided into seven parts (each part 2ml), 0.1µml, 1.0µml & 3.0µml concentration of melatonin were added to the T1, T2 and T3 respectively, L-arginine were added to the T4, T5 and T6 in 0.001µmol, 0.1µmol and 1.0µml concentration respectively while T7 serve as a control without any addition. All treatments cooled at 4°c. Then semen parameters evaluated. It was concluded from this study that addition of 0.1 µmol melatonin significantly protected ram sperm cell from cold storage that induced negative effects on sperm function. However the addition of L-arginine have no beneficial effect on cooled ram semen.